FAKTOR-FAKTOR YANG MEMPENGARUHI KEPERCAYAAN DAN LOYALITAS NASABAH PERBANKAN DI SURABAYA - Gunarto Suhardi (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2006)
Led by foreign banks operating in Indonesia, many banks have switched their mainbusiness activities from corporate banking business to individual customer banking activities. This is due to the deteriorating general economic condition in Indonesia at the present time. Individual customer’s base operation for banking communities proved to be suitable and giving good returns. However, as many banks operating in the same basis, competition among banks has mounted considerably. One must be able to achieve trust and loyalty from their valued customers. This article tries to understand how bank in Surabaya should get these basic elements of trust and loyalty.Keywords: corporate banking business, individual customer banking, trust, loyalty.